Floristic study of the pinion pine communities of Pinus pinceana Gordon - Villarreal Quintanilla, José Ángel; Mares Arreola, Oscar; Cornejo Oviedo, Eladio; Capó Arteaga, Miguel A. (Instituto de Ecología, A.C., 2009)
A floristic study of 14 communities with Pinus pinceana Gordon was carried out. This species is distributed in small populations along the Sierra Madre Oriental in northern and central Mexico. A floristic similarity analysis between localities is included. A total of 446 species (plus 4 infaespecific taxa), 247 genera and 78 families were found. The communities can be separated by its flora into two groups: the northern one, located in Coahuila, Zacatecas and San Luis Potosí, and the southern one located in Querétaro and Hidalgo.